Effectiveness of the TAK-003 Dengue Vaccine in Preventing Dengue Infection in Children: A Systematic Review - Hisyam Hartaman; Mishbakhul Luthfi; Rahmat Hidayat Nur Ilhami; Sri Wahyuni Evi Nafisyah (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
BACKGROUND: Dengue fever remains an important global health issue, particularly among children. Developing an effective and safe vaccination against all four dengue virus serotypes is still a challenge. TAK-003 is a tetravalent vaccination candidate based on a live attenuated DENV-2 virus with great efficacy and a favorable safety profile. METHOD: This systematic review was conducted using the PRISMA 2020 guidelines and a literature search of the PubMed, Scopus, and Wiley databases until October 15, 2025. Clinical trials and observational studies evaluating TAK-003's efficacy and safety in children were among the inclusion criteria. The risk of bias was assessed using ROB 2.0 and the Newcastle-Ottawa Scale. RESULTS: Out of 132 publications evaluated, four unique studies (2 RCTs, 1 single-arm study, and 1 case-control trial) fulfilled the inclusion criteria. A phase III clinical trial (NCT02747927) of 20,099 children aged 4 to 16 years found an overall vaccination effectiveness of 73.3% against symptomatic dengue, with the strongest protection against DENV-2 (95.1%) and DENV-1 (69.8%). Follow-up results for up to 4.5 years after vaccination showed continuous long-term efficacy, including protection in people seronegative for DENV-1 and DENV-2. CONCLUSION: TAK-003 has been found to be safe, immunogenic, and effective in avoiding symptomatic and severe dengue in children and adolescents living in both endemic and non-endemic countries. This vaccine has tremendous potential as a global dengue preventive strategy, while protection against DENV-3 and DENV-4 need further improvement.